Tjieng Tjang Tjerries and other stories by Jolyn Phillips - Naledi Msimang (Journal of BRICS Studies)
Tjieng, Tjang, Tjerries is a collection of thirteen (13) short stories set in Gansbaai, a working-class fishing town in the Western Cape, South Africa. Jolyn Phillips covers the stories of many of its residents. Phillips paints a colourful picture of the residents in the town and the issues that occupy their attention. She stays true to the characters of the town representing them as they are, warts and all. For all this, she handles her characters with care, and even affection. She stays true even to the mix of English and Afrikaans spoken in the town, and code-switches from one language to the other regularly and unapologetically so. The stories in turn cover issues concerning domestic violence, drug abuse, poverty, mental health issues and religion, amongst others. While these are commonplace in many South African communities like Gansbaai, Phillips’ stories also, perhaps importantly, focus on interactions between families and amongst the community members, social attitudes towards each other, family secrets, taboos, colorism, death, town life/the geography of the town (the sea) that are peculiar to the town and to coloured people.